2022
DOI: 10.3390/agriculture12050715
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Population Aging and Renewable Energy Consumption on Agricultural Green Total Factor Productivity in Rural China: Evidence from Panel VAR Approach

Abstract: China is moving toward the important goal of being a green and low-carbon country, and the current severity level of population aging is of particular concern to the government. Aging, renewable energy consumption, and technological progress are closely linked. In this research, a panel vector autoregressive (PVAR) model is employed to investigate the long-run equilibrium relationship between population aging, renewable energy consumption and agricultural green total factor productivity using panel data for 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…For example, Liu et al [39] investigated the determinants of agricultural TFP in China and found that the elderly population had a significant and positive impact on technical efficiency improvement. Similarly, Li et al [43] found that population aging impacted positively agricultural GTFP in China. From a micro perspective, a case study using microdata of the assembly plant of truck manufacturing by Börsch-Supan and Weiss [42] showed that the average age-productivity profile of workers increased until age 65.…”
Section: Research On the Impact Of Aging On Productivitymentioning
confidence: 90%
See 1 more Smart Citation
“…For example, Liu et al [39] investigated the determinants of agricultural TFP in China and found that the elderly population had a significant and positive impact on technical efficiency improvement. Similarly, Li et al [43] found that population aging impacted positively agricultural GTFP in China. From a micro perspective, a case study using microdata of the assembly plant of truck manufacturing by Börsch-Supan and Weiss [42] showed that the average age-productivity profile of workers increased until age 65.…”
Section: Research On the Impact Of Aging On Productivitymentioning
confidence: 90%
“…However, from a positive research perspective, aging is seen to raise total factor productivity (TFP) because of investment in human capital and knowledge accumulation. Specifically, the ever-growing aging population promotes opportunities for an increase in human capital investment to reduce the dampening effect of aging on productivity, i.e., population aging promotes productive capacity [43]. Compared to younger workers, older workers usually have more experience in production and can make fuller use of their experience to increase productivity.…”
Section: Research On the Impact Of Aging On Productivitymentioning
confidence: 99%
“…The index could effectively avoid the possibility of no solution, meet the requirements of circularity, as well as allow technical regression. The global benchmark enveloped the whole current benchmark into a single set of global production possibilities, serving as a common reference set for each period [ 30 , 31 ]. The sets of production possibilities for current and global benchmarks were shown as follows: The current benchmark: The global benchmark: …”
Section: Methodsmentioning
confidence: 99%
“…Considering the homogeneity and accessibility of the data statistical caliber, the study compiled the relevant data from 31…”
Section: Data Sourcesmentioning
confidence: 99%
“…Existing studies have empirically tested that implementing crop insurance, carbon trading systems, and other agricultural environment protection policies can help increase AGTFP [ 18 , 19 , 34 ]. In addition, the use of new technologies is also a significant driving force for the sustained growth of AGTFP, including renewable energy consumption, the spread of Internet technologies, and the development of inclusive digital finance [ 35 , 36 , 37 ]. Some scholars have also studied the influencing factors that hinder the growth of AGTFP, including factor market distortion, resource mismatch, farmland pollution, agricultural disasters, and climate change [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%